NICKELOAN TOURMALINE FROM THE BEREZOVSKOE GOLD DEPOSIT, MIDDLE URALS, RUSSIA - Baksheev I.A.; Kudryavtseva O.E. (My University, 2004)
Nickeloan tourmaline (up to 0.531 apfu Ni) associated with nickeloan talc (0.511‐0.582 apfu Ni) or chromian muscovite is developed in magnesite‐quartz veins hosted in ultramafic talc + magnesite ± hematite ± chromian muscovite hydrothermal alteration located in Uspenskaya Gorka, eastern flank of the Berezovskoe gold deposit, Middle Urals, Russia. The unusual Nirich composition of the silicates reflects the geochemical environment of formation. Tourmalines are represented by light and dark green needles in aggregates up to 2 cm in length. Crystals are characterized by a strong pleochroism, from colorless to green. Tourmaline cores associated with talc are magnesiofoitite with an elevated Na content (0.436‐0.452 apfu) and a Mg/(Fetot + Mg) value of 0.90, or dravite [Na 0.535‐0.765 apfu, Mg/(Fetot + Mg) 0.87‐0.88]. In the magnesiofoitite, Ni and Cr contents range from 0.060 to 0.425 apfu, and from 0.214 to 0.249 apfu, respectively. In the dravitic cores, Ni and Cr contents range from 0.077 to 0.102 apfu and from 0.000 to 0.272 apfu, respectively. Intermediate and rim zones are magnesiofoititic and dravitic [Na 0.443‐ 0.938 apfu, Mg/(Fetot + Mg) 0.74‐0.90]. Ni and Cr contents in the same zones range from 0.020 to 0.531 apfu, and from 0.188 to 0.449 apfu. The distribution of the Mg/(Fetot + Mg) within single crystals is oscillatory. Partition coefficients for Ni and Fetot between tourmaline and talc are 0.05 and 21.48, respectively. Tourmaline associated with chromian muscovite can be classified as dravite (0.669‐0.936 apfu Na), with Mg/(Fetot + Mg) ranging from 0.76 to 0.89. Some crystals are enriched in Cr (up to 1.564 apfu); Ni content ranges from 0.036 to 0.217 apfu. The Mossbauer study indicates that about half of the total Fe is Fe 3+
Keywords: nickeloan tourmaline; nickeloan talc; chromian muscovite; ultramafic talc–carbonate alteration; Berezovskoe gold deposit; Urals; Russia